Cell Cycle M-Phase Genes Are Highly Upregulated in Anaplastic Thyroid Carcinoma - Weinberger, Paul (Thyroid, 2017)
Background: Anaplastic thyroid carcinoma (ATC) accounts for only 3% of thyroid cancers, yet strikingly, it accounts for almost 40% of thyroid cancer deaths. Currently, no effective therapies exist. In an effort to identify ATC-specific therapeutic targets, we analyzed global gene expression data from multiple studies to identify ATC-specific dysregulated genes. Methods: The National Center for Biotechnology Information Gene Expression Omnibus database was searched for high-throughput gene expression microarray studies from human ATC tissue along with normal thyroid and/or papillary thyroid cancer (PTC) tissue. Gene expression levels in ATC were compared with normal thyroid or PTC using seven separate comparisons, and an ATC-specific gene set common in all seven comparisons was identified. We investigated these genes for their biological functions and pathways. Results: There were three studies meeting inclusion criteria, (including 32 ATC patients, 69 PTC, and 75 normal). There were 259 upregulated genes and 286 downregulated genes in ATC with at least two-fold change in all seven comparisons. Using a five-fold filter, 36 genes were upregulated in ATC, while 40 genes were downregulated. Of the 10 top globally upregulated genes in ATC, 4/10 (MMP1, ANLN, CEP55, and TFPI2) are known to play a role in ATC progression; however, 6/10 genes (TMEM158, CXCL5, E2F7, DLGAP5, MME, and ASPM) had not been specifically implicated in ATC. Similarly, 3/10 (SFTA3, LMO3, and C2orf40) of the most globally downregulated genes were novel in this context, while 7/10 genes (SLC26A7, TG, TSHR, DUOX2, CDH1, PDE8B, and FOXE1) have been previously identified in ATC. We experimentally validated a significant correlation for seven transcription factors (KLF16, SP3, ETV6, FOXC1, SP1, EGFR1, and MAFK) with the ATC-specific genes using microarray analysis of ATC cell lines. Ontology clustering of globally altered genes revealed that “mitotic cell cycle” is highly enriched in the globally upregulated gene set (44% of top upregulated genes, p-value <10(−30)). Conclusions: By focusing on globally altered genes, we have identified a set of consistently altered biological processes and pathways in ATC. Our data are consistent with an important role for M-phase cell cycle genes in ATC, and may provide direction for future studies to identify novel therapeutic targets for this disease.